The impact of battery operating temperature and state of charge on the lithium-ion battery internal resistance - Mahmud, Amirul Haniff (Penerbit UTM Press, 2017)
This paper studies the behaviour of the lithium-ion battery used in automotive application especially for electric vehicles (EVs) and hybrid electric vehicle (HEVs) by focusing on the impact of battery operating temperature and state of charge (SOC) on the battery internal resistance. An electrical battery model is used and developed in MATLAB/Simulink. The validation process was done by comparing the simulation results from the developed model with experiment results established by other researchers. From the comparison, it is shown that the developed model is able to predict the performance of the battery in terms of battery internal resistance in the function of operating temperature between 0 oC and 50oC and SOC range of 0.1 to 0.9. The internal resistance of lithium-ion battery minimum when the operating temperature is 30oC and SOC is 0.4.